Bahasa, Struktur Persajakan, dan Makna Moral dalam Syair Nasyid Karya Kiyai Hamzanwadi - Fitria Hairani; Lalu Fakihuddin (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
Researchers analyzed five songs (from the word choice, rhyme patterns, and moral). This research refers to qualitative research, the research method that is based on the philosophy postpositivisme, used to examine the condition of natural objects, (as his opponent was an experiment) where the researcher is a key instrument, the data collection techniques of triangulation (combined), data analysis inductive / qualitative, and the results qualitative research emphasizes meaning rather than generalization. The five songs were obtained from a source book nasyid songs work works chaplain Tuan Guru Haji Muhammad Zainuddin Abdul Madjid. The nature of the world literature as an autonomous cause of literary works has the right to be analyzed regardless of social background that produced it. Data collected from the research field of tangible words and not a series of numbers, so that the form of analysis using a structured approach to qualitative descriptions into expanded text and deep. All the activities of this analysis is an analysis that considers the meaning behind the meaning of social facts found in the field as well as literature. Researchers found that synonymous words and berantonim, has a very high artistic value, style with high aesthetic value and not least for the benefit of the people who are full of moral message, especially for the people of Sasak and Indonesian Muslims in general.